Preparation method of zirconium-doped ternary positive electrode material, ternary positive electrode material and application thereof

By doping zirconium into the ternary positive electrode material, using its larger ion radius and low migration structure free energy, problems such as lithium-nickel mixed discharge in nickel-rich ternary positive electrode material are solved, and more stable and efficient electrochemical performance is achieved .

CN115911355BActive Publication Date: 2025-02-07EVE POWER CO LTD

Patent Information

Application Number
CN202211726223.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-02-07
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing nickel-rich ternary positive electrode materials have problems such as lithium-nickel mixed displacement, structural phase transition, microcracks and oxygen loss, resulting in the decay of the electrode material capacity and the thermal effect of the battery.

Method used

By doping zirconium in the ternary positive electrode material, the larger ion radius and low migration structure free energy of Zr4+ are used to increase the lithium layer spacing, promote the diffusion of Li+, and reduce the lithium-nickel mixed discharge through electrostatic repulsion. The specific method includes first forming a first precursor of a certain size through a co-precipitation reaction, then depositing a zirconium-containing compound on its surface, and finally calcining through high-temperature solid phase to migrate the ionic solid phase to achieve uniform doping.

Benefits of technology

The uniform distribution of zirconium elements in the ternary positive electrode material and the adjustability of doping amount are improved, the stability and electrochemical performance of the material are enhanced, and the cycle characteristics and discharge specific capacity of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911355B_ABST
    Figure CN115911355B_ABST
Patent Text Reader

Abstract

According to one aspect of the present invention, a method for preparing a zirconium-doped ternary positive electrode material is provided, comprising the following steps: S1. According to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, a first precursor is prepared by a first coprecipitation reaction using a soluble nickel salt, a soluble cobalt salt and a soluble salt containing the M element, wherein the first precursor contains nickel element, cobalt element and M element, wherein the M element includes at least one of manganese element and aluminum element; S2. A zirconium-containing compound is deposited on the surface of the first precursor by a second coprecipitation reaction to obtain a second precursor; S3. According to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, the second precursor is mixed with a lithium source to obtain a third precursor, and the third precursor is calcined by a high-temperature solid phase method to obtain the zirconium-doped ternary positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to lithium ion battery technology, and in particular relates to a preparation method of a zirconium-doped ternary positive electrode material, the ternary positive electrode material and applications thereof. Background Art

[0002] In recent years, nickel-rich ternary materials have attracted much attention due to their high reversible capacity. However, nickel-rich ternary materials have problems such as lithium-nickel mixing, structural phase transition, microcracks and oxygen loss. These problems can lead to capacity decay of electrode materials and thermal effects of batteries. In order to improve the above problems, many effective solutions have been explored, and electrolyte optimization, surface coating and metal ion doping have been proven to be feasible strategies. Among them, metal ion doping is the introduction of ions of different valence states into the lattice, such as K + Mg 2+ , Ga 3+ 、Al 3+ 、Zr 4+ 、Ti 4+ , Nb 5+ , different metal ions can occupy different crystal positions, thereby improving the structural stability of the material.

[0003] Therefore, by doping Ni 2+ 、Co 3+ , Mn 4+ Metal ions with large ionic radius occupy part of the lithium site, ensuring that Ni 2+ While not occupying lithium sites, it further expands the unit cell parameters and interlayer spacing of the positive electrode material, thereby improving the stability of the nickel-rich ternary material.

[0004] Due to Zr 4+ The ionic radius is larger than that of Ni 2+ 、Co 3+ , Mn 4+ The ionic radius is large, and doping zirconium in the ternary cathode material can increase the lithium interlayer distance and promote Li + diffusion; in addition, Zr 4+ The migration structure free energy is lower than Ni 4+ , so Zr 4+ It is easier to migrate to the lithium layer; and the lithium layer has Zr 4+ After Zr 4+ Will be with you 4+ Strong electrostatic repulsion is generated between them, which hinders Ni 4+ Migrate to the lithium layer to reduce lithium-nickel mixing. Therefore, zirconium doping can be selected for the ternary positive electrode material to improve the stability of the ternary positive electrode material. Summary of the invention

[0005] In order to improve the stability of ternary positive electrode materials, the purpose of the present invention is to provide a method for preparing a zirconium-doped ternary positive electrode material, a ternary positive electrode material and applications thereof.

[0006] According to one aspect of the present invention, a method for preparing a zirconium-doped ternary positive electrode material is provided, comprising the following steps: S1. According to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, a first precursor is prepared by a first coprecipitation reaction using a soluble nickel salt, a soluble cobalt salt and a soluble salt containing the M element, wherein the first precursor contains nickel element, cobalt element and M element, wherein the M element includes at least one of manganese element and aluminum element; S2. A zirconium-containing compound is deposited on the surface of the first precursor by a second coprecipitation reaction to obtain a second precursor; S3. According to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, the second precursor is mixed with a lithium source to obtain a third precursor, and the third precursor is calcined by a high-temperature solid phase method to obtain the zirconium-doped ternary positive electrode material.

[0007] At present, the common zirconium doping methods include the following three methods: one is to dope zirconium by ball milling after the precursor is prepared; the second is to dope zirconium by stirring in an ethanol solution after the precursor is prepared; the third is to prepare a zirconium-doped ternary positive electrode material precursor by coprecipitation reaction by feeding the main elements of nickel, cobalt and manganese and the doping element zirconium at the same time. The applicant found that the preparation of the precursor by ball milling can only allow the zirconium element to be doped on the surface of the material, and the zirconium element is unevenly distributed; and for the second preparation scheme, the use of zirconium doping in ethanol solvent will consume a large amount of ethanol, which will not only increase the preparation cost, but also make the prepared precursor absorb moisture, causing the precursor to be more easily oxidized; and for the scheme of feeding at the same time, the four elements of nickel, cobalt, manganese and zirconium are fed at the same time for precipitation, and the arrangement of zirconium in the ternary positive electrode material cannot be controlled, and the structure of the obtained precursor has a high degree of uncertainty.

[0008] In the present invention, a first precursor with a certain size is first formed through a first coprecipitation reaction, and the formed first precursor has a flaky structure, and then a second coprecipitation reaction is performed to allow the zirconium-containing compound to adhere to the flaky structure on the surface of the first precursor to obtain a second precursor; then, a high-temperature calcination solid phase reaction is performed to cause the zirconium element attached to the surface of the second precursor to undergo ion solid phase migration, thereby completing the doping of the zirconium element in the ternary positive electrode material. Compared with the existing doping methods, the preparation method provided by the present invention can not only effectively improve the uniform distribution of the zirconium element in the ternary positive electrode material to which it is doped, but also improve the controllability of the zirconium element doping amount, so as to improve the quality stability of the zirconium-doped ternary positive electrode material, as well as the product cycle characteristics and discharge specific capacity.

[0009] Preferably, the particle size of the first precursor is 5 to 10 μm, and the particle size of the zirconium-containing compound is ≤ 100 nm. For example, the particle size of the first precursor is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, and the particle size of the zirconium-containing compound is 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm.

[0010] Preferably, the zirconium-containing compound includes at least one of zirconium dioxide and zirconium sulfate.

[0011] Preferably, in the zirconium-doped ternary cathode material, the doping amount of zirconium is 0.1-1%. For example, the doping amount of zirconium is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, etc.

[0012] Preferably, the operation of S1 is: according to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, a soluble nickel salt, a soluble cobalt salt, and a soluble salt containing the M element are dissolved in water to obtain a mixed metal salt solution, wherein the sum of the amounts of nickel element, cobalt element and M element in the mixed metal salt solution is 1 to 3 mol / L, the mixed metal salt solution, the precipitant and the complexing agent are mixed, and the mixed solution obtained is used as a first mixed solution, and then the first mixed solution is reacted under a nitrogen atmosphere to obtain a first precursor. For example, the sum of the amounts of nickel, cobalt and M in the mixed metal salt solution is 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L or 3 mol / L, etc.

[0013] Preferably, in S1, according to the volume ratio, the mixed metal salt solution: precipitant = 1 to 3: 1 to 2. For example, the mixed metal salt solution: precipitant = 1: 1, the mixed metal salt solution: precipitant = 1: 1.5, the mixed metal salt solution: precipitant = 1: 2, the mixed metal salt solution: precipitant = 1.5: 1, the mixed metal salt solution: precipitant = 1.5: 1, the mixed metal salt solution: precipitant = 1.5: 2, the mixed metal salt solution: precipitant = 2: 1, the mixed metal salt solution: precipitant = 2: 1.5, the mixed metal salt solution: precipitant = 2: 2, the mixed metal salt solution: precipitant = 2.5: 1, the mixed metal salt solution: precipitant = 2.5: 1.5, the mixed metal salt solution: precipitant = 2.5: 2, the mixed metal salt solution: precipitant = 3: 1, the mixed metal salt solution: precipitant = 3: 1.5 or the mixed metal salt solution: precipitant = 3: 2, etc.

[0014] Preferably, the precipitant comprises at least one of sodium hydroxide and sodium carbonate.

[0015] Preferably, the concentration of the precipitant is 1 to 3 mol / L. For example, the concentration of the precipitant is 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L or 3 mol / L.

[0016] Preferably, the complexing agent is added to adjust the pH to 10.5 to 11.5. For example, the complexing agent is added to adjust the pH of the first mixed solution to 10.5, 10.6, 10.7, 10.8, 10.9, 11, 11.1, 11.2, 11.3, 11.4 or 11.5.

[0017] Preferably, the complexing agent includes at least one of ammonia water and ammonium oxalate.

[0018] Preferably, the concentration of the complexing agent is 3 to 6 mol / L. For example, the concentration of the complexing agent is 3 mol / L, 3.1 mol / L, 3.2 mol / L, 3.3 mol / L, 3.4 mol / L, 3.5 mol / L, 3.6 mol / L, 3.7 mol / L, 3.8 mol / L, 3.9 mol / L, 4 mol / L, 4.1 mol / L, 4.2 mol / L, 4.3 mol / L, 4.4 mol / L, 4.5 mol / L, 4.6 mol / L, 4.7 mol / L, 4.8 mol / L, 4.9 mol / L, 5 mol / L, 5.1 mol / L, 5.2 mol / L, 5.3 mol / L, 5.4 mol / L, 5.5 mol / L, 5.6 mol / L, 5.7 mol / L, 5.8 mol / L, 5.9 mol / L or 6 mol / L, etc.

[0019] Preferably, the soluble nickel salt includes at least one of nickel sulfate, nickel chloride and nickel nitrate; and / or, the soluble cobalt salt includes at least one of cobalt sulfate, cobalt chloride and cobalt nitrate; and / or, the soluble salt containing the M element includes at least one of sulfate, chloride and nitrate.

[0020] Preferably, there is only one non-metallic anion in the mixed metal salt solution.

[0021] Preferably, in S1, the nitrogen flow rate is maintained at 40-80 mL / min. For example, the nitrogen flow rate is 40 mL / min, 45 mL / min, 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, 75 mL / min or 80 mL / min.

[0022] Preferably, in S1, the reaction temperature of the first coprecipitation reaction is 50-55°C, and after the feeding is completed, the reaction system is allowed to stand for 4-12 hours; the reaction temperature of the second coprecipitation reaction is 50-55°C, and after the feeding is completed, the reaction system is allowed to stand for 2-6 hours. For example, the reaction temperature of the first coprecipitation reaction is 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc., the standing time of the first coprecipitation reaction is 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, etc., the reaction temperature of the second coprecipitation reaction is 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc., and the standing time of the second coprecipitation reaction is 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, etc.

[0023] Preferably, the zirconium-containing compound is zirconium dioxide. Zirconium dioxide has a strong Zr-O bond, so zirconium doping can reduce the release of lattice oxygen in the ternary positive electrode material.

[0024] Preferably, in S2, the zirconium-containing compound is 0.2-2% of the sum of the amounts of the added soluble nickel salt, soluble cobalt salt and soluble salt containing element M, calculated by the ratio of the amounts of the substances. For example, the zirconium-containing compound is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0% of the sum of the amounts of the added soluble nickel salt, soluble cobalt salt and soluble salt containing element M, etc.

[0025] Preferably, the operation of S3 is: in the high temperature solid phase method involved in S3, the third precursor is first heated to 450-500°C at a heating rate of 1-10°C / min, and kept warm for 5-10 hours to obtain a pre-reaction product, and then the pre-reaction product is heated to 750-900°C at a heating rate of 1-10°C / min, and kept warm for 12-24 hours, thereby obtaining a zirconium-doped ternary positive electrode material. For example, the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.; the third precursor is heated to 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C or 500°C, etc.; the first insulation time is 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h, etc.; the pre-reaction product is heated to 750 ℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃ or 900℃, etc.; the second insulation time is 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, 20h, 20.5h, 21h, 21.5h, 22h, 22.5h, 23h, 23.5h or 24, etc.

[0026] Preferably, the lithium source includes at least one of lithium hydroxide and lithium carbonate.

[0027] Preferably, in S3, the mass ratio of lithium source: second precursor is 1.03-1.05: 1. For example, the mass ratio of lithium source: second precursor is 1.03: 1, 1.04: 1 or 1.05: 1.

[0028] According to one aspect of the present invention, a ternary positive electrode material is provided, and the ternary positive electrode material is prepared by any of the above-mentioned methods for preparing zirconium-doped ternary positive electrode materials. The prepared ternary positive electrode material has the following two advantages: on the one hand, the lithium-nickel mixing effect is weakened, which can reduce the side reaction between the electrode and the electrolyte, thereby improving the stability of the ternary positive electrode material; on the other hand, the transmission of lithium ions and charges in the electrode is accelerated, and the lithium ion diffusion coefficient of the ternary positive electrode material is also improved, so that the prepared zirconium-doped ternary positive electrode material exhibits excellent electrochemical performance.

[0029] According to another aspect of the present invention, a ternary positive electrode is provided, comprising a current collector and a positive electrode active coating disposed on the surface of the current collector, wherein the positive electrode active coating contains the above-mentioned ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the EDS mapping diagram of the ternary cathode material prepared in Example 3;

[0031] Figure 2 The XRD diagram of the ternary cathode material is measured, wherein AC is a control sample without zirconium doping, and the zirconium doping amount of the zirconium element in the ternary cathode material doped with zirconium is 0.1-1%;

[0032] Explanation of reference numerals: (a). XRD spectrum of the test sample in the range of 3° to 90°; (b). XRD pattern of the test sample in the range of 18° to 19°. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] Example 1

[0035] 1. Preparation method

[0036] S1. Prepare 2 mol / L sodium hydroxide solution, and calculate according to the molar ratio, take nickel sulfate hexahydrate: cobalt sulfate heptahydrate: manganese sulfate monohydrate = 6:2:2 and dissolve them in water to prepare a mixed metal salt solution with a concentration of 1 mol / L, then turn on the stirring paddle of the reactor, add the above mixed metal salt solution and 2 mol / L sodium hydroxide solution to the reactor, calculate according to the volume ratio, mixed metal salt solution: sodium hydroxide solution = 2:1, then add an appropriate amount of 3 mol / L ammonia water, adjust the pH to 11.5, heat to 60°C under a nitrogen atmosphere for reaction for 12 hours, and then keep it warm and stand for 8 hours to obtain a first precursor, wherein the nitrogen introduction rate is maintained at 70 mL / min;

[0037] S2. Add zirconium dioxide with a particle size of 100 nm to the reactor (calculated according to the ratio of the amount of substance, zirconium dioxide is 0.1% of the sum of the amount of the added nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate monohydrate), heat to 60°C, stir and disperse for 2 hours, keep warm and stand for 2 hours, during which the nitrogen flow rate is maintained at 70 mL / min. After the reaction is completed, filter the reaction solution, wash the obtained solid repeatedly with water until the pH of the washing solution is 7, and then filter again and freeze-dry the obtained solid to obtain the second precursor;

[0038] S3. Lithium hydroxide is mixed with the second precursor to obtain a third precursor, wherein, calculated by mass ratio, lithium hydroxide: second precursor = 1.05:1. The third precursor is calcined in a tubular furnace under an oxygen atmosphere, heated to 480°C at a heating rate of 5°C / min, and kept warm for 5 hours. Subsequently, it is heated to 850°C at a heating rate of 5°C / min, and kept warm for 20 hours. The obtained powder is sieved through a 200-mesh sieve to obtain a zirconium-doped ternary positive electrode material.

[0039] Examples 2 to 5 refer to the formula and method provided in Example 1 to prepare ternary positive electrode materials, with the percentage of the amount of zirconium dioxide added to the mixed metal salt used in the formula to prepare the ternary positive electrode material as a variable. The variables used in Examples 2 to 5 to prepare the ternary positive electrode materials are shown in Table 2. Except for the above differences, the operating steps for preparing the ternary positive electrode materials in Examples 2 to 5 are strictly consistent with those in Example 1.

[0040] Table 1. Variables for preparing ternary positive electrode materials in Examples 1 to 5

[0041]

[0042] Test Example 1

[0043] 1. Test subjects

[0044] Using the ternary cathode materials prepared in Examples 1 to 5, a battery was prepared for testing, as described in detail below:

[0045] According to the mass ratio, the ternary positive electrode material: Super P: PVDF = 95: 2.5: 2.5 is mixed with an appropriate amount of NMP solvent to prepare an electrode slurry, which is then evenly coated on the surface of the aluminum foil and dried to obtain a positive electrode plate; the electrolyte used is a mixture of ethylene carbonate and dimethyl carbonate dissolved with 1 mol / L LiPF6, wherein, according to the volume ratio, ethylene carbonate: dimethyl carbonate = 1:1. The prepared positive electrode plate, negative electrode plate (lithium plate) and electrolyte are combined into a battery for testing.

[0046] 2. Test Method

[0047] (1) Doping amount of zirconium: SEM test was performed using JEOL JSM-7610F at 20 kV to obtain the morphology of the prepared ternary cathode material. The morphology of the ternary cathode material and the distribution of each element were observed under dark field using EDS mapping data measured by JEM-200F.

[0048] (2) XRD: X-ray diffraction patterns of samples were measured by Ultima IV (Rigaku, Japan). The ternary cathode material was spread until the sample holder was covered, with a test rate of 5° / min and a test angle 2θ ranging from 3° to 90°.

[0049] (3) Cyclic charge and discharge test: At 25°C, the prepared battery was charged at a 3C rate and discharged at a 3C rate in the voltage range of 2.5 to 4.3 V. A full charge and discharge cycle test was performed for 400 cycles, and the capacity retention rate and discharge specific capacity were recorded.

[0050] 3. Experimental results and analysis

[0051] The cyclic charge and discharge test results of Test Example 1 are shown in Table 2, where it can be found that in the zirconium-doped ternary positive electrode materials prepared in Examples 1 to 5, as the zirconium doping amount in the ternary positive electrode material increases, the capacity retention rate of the battery prepared using the zirconium-doped ternary positive electrode material shows a trend of first increasing and then decreasing. The battery capacity retention rate prepared by the zirconium-doped ternary positive electrode material prepared in Example 3 is the highest, which indicates that the optimal zirconium doping amount of the ternary positive electrode material provided by the present invention is 0.5%. The EDS mapping and XRD test results of the zirconium-doped ternary positive electrode material prepared in Example 3 are shown as follows: Figure 1 , Figure 2 As shown, EDS mapping analysis ( Figure 1 ), we can see that the distribution uniformity of nickel, cobalt, manganese and zirconium in the test objects is relatively high, while Figure 2The disappearance of the 003 peak and the appearance of a new peak in (b) indicate that the zirconium element is successfully doped in the ternary positive electrode material. From the test results, it can be seen that the zirconium doping amount in the ternary positive electrode material prepared in Example 1 is low, while the zirconium doping amount in the ternary positive electrode material prepared in Example 5 is high. The corresponding battery capacity retention rates of both are lower than those of other embodiments, while the zirconium doping amount of the ternary positive electrode materials prepared in Examples 2 to 4 is 0.1 to 1%. The capacity retention rate of these ternary positive electrode materials is high, and the ternary positive electrode materials have good cycle stability.

[0052] Table 2. Experimental results of test case 1

[0053] Group Zirconium doping amount / % Capacity retention rate / 400cls <![CDATA[Discharge specific capacity / mAh·g -1 > Example 1 0.05 69.0% 94.2 Example 2 0.1 69.5% 104.7 Example 3 0.5 79.7% 118.8 Example 4 1 75.8% 109.8 Example 5 2 61.8% 93.4

[0054] Example 6

[0055] This embodiment prepares the ternary positive electrode material with reference to the formula and method provided in Embodiment 3. The difference from Embodiment 3 is that the stoichiometric ratio of Ni:Co:Mn in S1 for preparing the ternary positive electrode material is 8:1:1; in S3, the material is heated to 480°C at a heating rate of 5°C / min, kept warm for 5h, and then heated to 800°C at a heating rate of 5°C / min. Except for the above differences, the operating steps for preparing the ternary positive electrode material in this embodiment are strictly consistent with those in Embodiment 3.

[0056] Example 7

[0057] This embodiment prepares the ternary positive electrode material with reference to the formula and method provided in Embodiment 3. The difference from Embodiment 3 is that the stoichiometric ratio of the ternary positive electrode material used in S1 is Ni:Co:Mn=5:2:3; in S3, the material is heated to 480°C at a heating rate of 5°C / min, kept warm for 5h, and then heated to 900°C at a heating rate of 5°C / min. Except for the above differences, the operating steps for preparing the ternary positive electrode material in this embodiment are strictly consistent with those in Embodiment 3.

[0058] Example 8

[0059] This embodiment prepares the ternary positive electrode material with reference to the formula and method provided in Embodiment 3. The difference from Embodiment 3 is that in S1, a mixed metal salt solution with a concentration of 1 mol / L is prepared by taking nickel sulfate hexahydrate: cobalt sulfate heptahydrate: anhydrous aluminum sulfate = 8:1.5:0.5; in S3, it is heated to 480°C at a heating rate of 5°C / min, kept warm for 5h, and then heated to 800°C at a heating rate of 5°C / min. Except for the above differences, the operating steps for preparing the ternary positive electrode material in this embodiment are strictly consistent with those in Embodiment 3.

[0060] Test Example 2

[0061] 1. Test subjects

[0062] Using the ternary positive electrode materials prepared in Examples 6 to 8, batteries were prepared for testing, specifically according to the method provided in Test Example 1.

[0063] 2. Test Method

[0064] The test was performed according to the method provided in Test Example 1.

[0065] 3. Experimental results and analysis

[0066] The experimental results of the test example are shown in Table 3. From the results of Test Example 2, it can be seen that the method for preparing zirconium-doped ternary positive electrode materials provided by the present invention can prepare various types of nickel-rich ternary materials, and the prepared ternary positive electrode materials have good stability.

[0067] Table 3. Experimental results of test case 2

[0068] Group Zirconium doping amount / % Capacity retention rate / 400cls <![CDATA[Discharge specific capacity / mAh·g -1 > Example 6 0.5 81.2% 119.7 Example 7 0.5 73.2% 111.7 Example 8 0.5 70.1% 108.3

[0069] Comparative Example 1

[0070] This comparative example prepares the ternary positive electrode material with reference to the formula provided in Example 3. The difference from Example 3 is that this comparative example adopts the ball milling method to prepare the ternary positive electrode material, specifically, as follows:

[0071] According to the formula provided in Example 3, nickel sulfate hexahydrate, cobalt sulfate heptahydrate, manganese sulfate monohydrate, zirconium dioxide and lithium hydroxide are put into a cylinder, and high-energy ball milling is carried out for 24 hours using a planetary ball mill. The ball-to-material ratio is 10:1, steel balls are used as grinding bodies, and the rotation speed is 400r / min. The obtained powder is subjected to a high-temperature solid-phase reaction, and the calcination operation is strictly consistent with S3 in Example 3, thereby obtaining a ternary positive electrode material.

[0072] Comparative Example 2

[0073] This comparative example prepares the ternary positive electrode material with reference to the formula provided in Example 3. The difference from Example 3 is that this comparative example adopts the ball milling method to prepare the ternary positive electrode material, specifically, as follows:

[0074] S1~S2. The operation is strictly consistent with S1 and S2 of Example 3;

[0075] S3. According to the formula provided in S3 of Example 3, lithium hydroxide and the second precursor are mixed and put into a cylinder, and a planetary ball mill is used for 24 hours of high-energy ball milling. The ball-to-material ratio is 10:1, and steel balls are used as grinding bodies. The rotation speed is 400r / min. The obtained powder is subjected to a high-temperature solid-phase reaction. The calcination operation is strictly consistent with S3 of Example 3, thereby obtaining a ternary positive electrode material.

[0076] Comparative Example 3

[0077] This comparative example prepares a ternary positive electrode material with reference to the formula provided in Example 3. The difference from Example 3 is that this comparative example uses an ethanol solution to prepare the ternary positive electrode material, specifically, as follows:

[0078] S1. The operation of S1 in Example 3 is strictly consistent;

[0079] S2. The first precursor prepared in S1 is dissolved in ethanol to obtain solution A, and then zirconium dioxide with a particle size of 100 nm is added (calculated according to the molar ratio, 1% of the added mixed metal salt), and the remaining operations are strictly consistent with the S2 operation of Example 3 to obtain a second precursor;

[0080] S3. The operation of S3 in Example 3 is strictly consistent to obtain a ternary positive electrode material.

[0081] Comparative Example 4

[0082] This comparative example prepares a ternary positive electrode material with reference to the formula provided in Example 3. The difference from Example 3 is that this comparative example adopts a co-current feeding co-precipitation method to prepare a ternary positive electrode material, specifically, as described below:

[0083] S1. According to the raw materials and ratios provided in Example 3, a mixed metal salt solution, zirconium dioxide, and sodium hydroxide solution were added simultaneously under a nitrogen atmosphere, followed by adding aqueous ammonia, adjusting the pH to 11.5, heating to 60 ° C under a nitrogen atmosphere for 12 h, and standing for 12 h to obtain a precursor;

[0084] S2. According to the formula provided in S3 of Example 3, the precursor is mixed with lithium hydroxide and then calcined. The calcination operation is strictly consistent with the operation of S3 of Example 3 to obtain a ternary positive electrode material.

[0085] Test Example 3

[0086] 1. Test subjects

[0087] Using the ternary positive electrode materials prepared in Example 3 and Comparative Examples 1 to 4, batteries were prepared for testing, specifically according to the method provided in Test Example 1.

[0088] 2. Test Method

[0089] Stability experiment: The preparation method described in Example 3 and Comparative Examples 1 to 4 was repeated three times, and the prepared ternary positive electrode materials were marked as sample 1, sample 2, and sample 3 respectively. The prepared samples were made into batteries, and the zirconium doping amount, capacity retention rate, and discharge specific capacity of different samples were tested. The variance of the measured data was then calculated respectively. The smaller the variance, the higher the repeatability of the corresponding preparation method.

[0090] The zirconium doping amount and the cyclic charge and discharge test were tested according to the method provided in Test Example 1.

[0091] 3. Experimental results and analysis

[0092] Through the stability experiment, it was found that, as shown in the data of Table 4 and Table 5, the repeatability of the ternary positive electrode material prepared in Example 3 is high, and the capacity retention rate is also high, indicating that the preparation method of Example 3 has high repeatability and the prepared ternary positive electrode material has good stability. This is because the doping process of Example 3 has high stability, and the zirconium element can be evenly dispersed in the prepared ternary positive electrode material. However, it can be seen from the data in Table 5 that the variance values ​​of Comparative Examples 1 to 4 are large, indicating that the experimental repeatability of Comparative Examples 1 to 4 is low, and the cyclic charge and discharge experiment shows that the experimental data of Comparative Examples 1 to 4 fluctuate greatly. This may be because there is an uneven dispersion of zirconium elements, and this uneven dispersion is uncontrollable, which in turn affects the stability of the electrode material and the battery. In addition, for Comparative Example 3, its discharge specific capacity is not very stable. This is because the use of ethanol to prepare the ternary positive electrode material causes the precursor to absorb moisture, which in turn causes the precursor to be more easily oxidized. However, the preparation method provided in Comparative Example 4 has poor quality control, resulting in large fluctuations in the capacity retention rate and discharge specific capacity data measured each time. This is due to the low structural stability of the prepared ternary positive electrode material.

[0093] Table 4. Experimental results of test case 3

[0094]

[0095]

[0096] Table 5. Calculation results for test case 3

[0097]

[0098] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a zirconium-doped ternary positive electrode material, characterized in that: The steps include: S1. According to the stoichiometric ratio of each element in the zirconium-doped ternary cathode material, a first precursor is prepared by a first coprecipitation reaction using a soluble nickel salt, a soluble cobalt salt and a soluble salt containing the M element, wherein the first precursor contains nickel, cobalt and manganese, and the stoichiometric ratio of the first precursor is Ni:Co:Mn=8:1:1; S2. Depositing zirconium dioxide on the surface of the first precursor by a second coprecipitation reaction to obtain a second precursor, wherein the particle size of the zirconium dioxide is ≤100 nm; S3. According to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, the second precursor is mixed with a lithium source to obtain a third precursor, and then heated to 480°C at a heating rate of 5°C / min, and kept warm for 5 hours, and then heated to 800°C at a heating rate of 5°C / min, and kept warm for 20 hours, thereby obtaining the zirconium-doped ternary positive electrode material; wherein, in the zirconium-doped ternary positive electrode material, the doping amount of zirconium is 0.5%.

2. The preparation method according to claim 1, characterized in that: The particle size of the first precursor is 5-10 μm.

3. The preparation method according to any one of claims 1 to 2, characterized in that The operation of S1 is: according to the stoichiometric ratio of each element in the zirconium-doped ternary positive electrode material, the soluble nickel salt, the soluble cobalt salt, and the soluble salt containing the M element are dissolved in water to obtain a mixed metal salt solution, wherein the sum of the amounts of the nickel element, the cobalt element and the M element in the mixed metal salt solution is 1-3 mol / L, the mixed metal salt solution, the precipitant and the complexing agent are mixed, and the mixed solution obtained is used as the first mixed solution, and then the first mixed solution is reacted under a nitrogen atmosphere to obtain the first precursor.

4. The preparation method according to claim 3, characterized in that: In S1, calculated by volume ratio, the mixed metal salt solution: the precipitant = 1-3: 1-2.

5. The preparation method according to claim 3, characterized in that: The amount of the complexing agent added is sufficient to make the pH of the first mixed solution equal to 10.5-11.

5.

6. The preparation method according to claim 3, characterized in that: The soluble nickel salt includes at least one of nickel sulfate, nickel chloride and nickel nitrate; And / or, the soluble cobalt salt includes at least one of cobalt sulfate, cobalt chloride and cobalt nitrate; And / or, the soluble salt containing the M element includes at least one of sulfate, chloride and nitrate.

7. The preparation method according to any one of claims 1 to 2, characterized in that: In S1, the reaction temperature of the first coprecipitation reaction is 50-55° C., and after the feeding is completed, the reaction system is allowed to stand for 4-12 hours; In S2, the reaction temperature of the second coprecipitation reaction is 50-55°C. After the feeding is completed, the reaction system is allowed to stand for 2-6 hours.

8. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the method for preparing a zirconium-doped ternary positive electrode material as claimed in any one of claims 1 to 7.

9. A ternary positive electrode, characterized in that: The ternary positive electrode comprises a current collector and a positive electrode active coating disposed on the surface of the current collector, wherein the positive electrode active coating contains the ternary positive electrode material as claimed in claim 8.

Citation Information

Patent Citations

  • Doped modified lithium nickel cobalt manganese material, preparation method thereof and lithium ion battery

    CN103296249A

  • High-nickel ternary positive electrode material of lithium ion battery and preparation method of high-nickel ternary positive electrode material

    CN105633395A

  • Gradient doping and surface modification method of single-crystal high-nickel lithium ion battery positive electrode material

    CN113745497A

Cited By

  • High-air-stability ternary positive electrode material based on two-step plasma technology and preparation method and application thereof

    CN122025614A

  • A high-air-stability ternary positive electrode material based on a two-step plasma technology, and a preparation method and application thereof

    CN122025614B